Quinazolinone derivatives - Hanusek, Jiří; Sedlák, Miloš (Univerzita Pardubice, 2002)
The presented review covers applications (especially medical and pharmaceutical), natural occurrence and the synthesis of quinazolin-2-one, quinazolin-4-one and quinazolin-2, 4-dione derivatives. The reaction mechanisms of the most interesting reactions are also discussed.
Keywords: quinazolinové deriváty; reakční mechanismy; syntézy; aplikace